Deradicalisation of Jobbik and its consequences – a visual ethnographic analysis of the symbolic and ritual change of a Hungarian radical right party. Issue 4 (2nd October 2022) - Hyttinen, Anniina
ABSTRACT: This article analyses the Hungarian populist radical right party Jobbik's deradicalisation process and its manifestations in the symbolic and ritual sphere. It contrasts visual ethnographic material collected during the national day commemorations in Budapest in 2013–2014 with new material collected in 2017–2019. Jobbik's controlled top-down-led moderation, aimed at widening the voter base, and moved the party from a strict ideological nativism towards a more flexible right-wing populism. However, stripping the party from its radicalism meant losing the rich nationalist symbolism, rituals, and the power and solidarity connected to them. Jobbik's transformation led to emptiness in the symbolic and ritual sphere, which used to be crucial for the radical right subculture that surrounded the party and its core supporters' self-identification. The deradicalisation process led also to the emergence of a radical right splinter party, Mi Hazánk, which quickly appropriated the nationalist and revisionist symbols earlier used by Jobbik.